Association between non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio and telomere length: the NHANES 1999–2002 - Liu, Mingjie; Wang, Chendong; Wei, Bai (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThe relationship between non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio (NHHR) and telomere length (TL) remains unclear. This study aims to investigate their association in a nationally representative US population.MethodsData from 6,342 adults aged ≥20 were obtained from the National Health and Nutrition Examination Survey (NHANES) 1999–2002. The NHHR was calculated and categorized into tertiles. TL was measured as the telomere-to-standard reference DNA ratio. Multivariate linear regression and smooth curve fitting were employed to assess the association between NHHR and TL.ResultsThe study population (mean age 45.1 ± 0.4 years, 48.9% male) was stratified into NHHR tertiles. Compared with the lowest NHHR tertile, the highest NHHR tertile was associated with adverse inflammatory and cardiometabolic profiles, including elevated white blood cell counts (6.88 ± 0.07–7.54 ± 0.08 × 109/L) and increased prevalence of hypertension (18.81%–25.71%) and diabetes (3.38%–7.17%). An elevated NHHR was significantly associated with a shorter TL (T/S ratio: 1.09 ± 0.02–1.03 ± 0.02; P = 0.0005). This association remained significant in partially adjusted models but was attenuated in a fully adjusted model. Significant interactions were observed for age and hypertension status.ConclusionThis study revealed a linear inverse association between NHHR and TL, suggesting the utility of the NHHR as a novel biomarker for biological aging. Further prospective studies are warranted to validate these findings.